Emerging scriptures: Torah, Gospel & Qur'an in Christian perspective - Schofield, Rodney (Mzuni books, 2014)
1. Many roads, one goal -- part 1. Reflecting on the Hebrew scriptures -- 2. The Jewish inheritance of Jesus and the early church -- 3. Valuing the Hebrew scriptures -- 4. Israel's history -- 5. Theological perspectives of the Hebrew bible -- 6. Messianic expectations -- part 2. Assessing the Christian writings -- 7. The earliest Christian witnesses -- 8. from oral testimony to written records -- 9. The emergence of Christian scripture -- 10. Ongoing formation of faith -- part 3. Responding to the Qur'an -- 11. Encountering the Qur'an -- 12. The people of the book -- 13. The seal of the prophets -- 14. Some Qur'anic themes -- 15. Early Christian responses -- Map of Arabia and her neighbours -- Epilogue -- 16. Dialogue today.